Gazeta Polska . pismo Konfederacji Polski Niepodległej, no. 64, 1989 - [ed. Krzysztof Król et al.] (Wydawnictwo Polskie, 1989)
Creation and circulation: After the introduction of the Martial Law, publication suspended in 1982-1985. Republished underground in 1986-1989. Republished again in 1992